Sustained disconnection in sensorimotor pathways results in poor motor function outcome in a term infant after severe white matter injury: A case report. Issue 31 (August 2018) - Son, Sunhan; Kang, Si Hyun; Lee, Na Mi; Kim, Don-Kyu; Seo, Kyung Mook; Ro, Hee Joon
Abstract: Introduction: We report a case of an infant with severe white matter injury (WMI), which was serially evaluated using diffusion tensor imaging (DTI). Case presentation: A male infant showed decreased muscle tone and weak breathing. A brain magnetic resonance imaging (MRI) 10 days after birth (first study) revealed diffuse microhemorrhages and encephalomalacia. DTI revealed lack of reconstruction of corticospinal tract (CSTs), minimal reconstruction of medial lemniscus, and related thalamocortical pathways (MLs) from the brain stem to the internal capsule level on the left side. The spinothalamic tract and related thalamocortical pathways (STTs) were reconstructed from the brain stem to the internal capsule level bilaterally. The second study one year later showed the absence of reconstruction of CSTs, but reconstruction of MLs and STTS from the brain stem to above the internal capsule showed increased visualization. The third study 3 years later still showed the absence of CSTs reconstruction and MLs and STTs showed no changes from the second study. During this 3-year observation period, the patient showed minimal motor development, and was unable to walk independently, although Gross Motor Function Measure (GMFM) scores were slightly increased. Lessons: Sustained disconnection of major sensorimotor pathways after WMI confirmed by DTI was used to predict motor function outcome.